Design and Development of a Website-Based Internship Information System Using the Personal Extreme Programming Method (Case Study: Sidoarjo Regency Communication and Informatics Service) - Muhammad Faiq Al Abiyyi; Nur Cahyo Wibowo; Seftin Fitri Ana Wati (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2026)
The management of the internship program at the Department of Communication and Informatics (Diskominfo) of Sidoarjo Regency is currently conducted manually. This conventional approach faces significant challenges regarding information transparency, the ease of monitoring daily activities, and the administration of program completion, necessitating a digital transformation to enhance service quality. This research aims to design and develop a web-based internship information system to automate the entire administrative process at Diskominfo Sidoarjo. The system development utilized the Personal Extreme Programming (PXP) method, encompassing the requirements phase, a planning phase that resulted in 28 user stories, as well as design, implementation, and system testing. Technically, the website was built using the Express.js framework and the React.js library. The result is a functional information system that provides features for internship data management, daily activity monitoring, and program completion administration. System testing was conducted using the black-box testing method, which demonstrated that all functionalities met the functional requirements of the users. Overall, the web-based internship information system at the Department of Communication and Informatics of Sidoarjo Regency was successfully developed using the Personal Extreme Programming approach.